Evaluations of perestroika in post-Soviet Central Asia: Public views in contemporary Uzbekistan, Kazakhstan and Kyrgyzstan. Issue 2 (June 2016) - Dadabaev, Timur
Abstract: This paper suggests that the different and sometimes contradictory public narratives of perestroika constitute an essential part of understanding the expectations of people regarding perestroika and their evaluation in the post-perestroika years. These narratives also underline the notion that post-Soviet governments have been unable to consolidate new constructs of memory with respect to perestroika. Historical construction regarding the pre-perestroika years of the Soviet administration in most of the post-Soviet Central Asian (CA) countries is conducted along the ideological lines associated with the post–independence years in each of the republics.